Complement-mediated kidney diseases. (December 2020) - Poppelaars, Felix; Thurman, Joshua M.
Highlights: Immune-complexes activate the classical pathway of complement in many forms of glomerulonephritis. The alternative and lectin pathways are also activated in several forms of kidney disease. Complement activation in the kidney can be detected by immunostaining of biopsy tissue and by examining complement levels in plasma. Therapeutic complement inhibitors are to be protective in several forms of kidney disease, and there are many ongoing clinical trials. Abstract: It has long been known that the complement cascade is activated in various forms of glomerulonephritis. In many of these diseases, immune-complexes deposit in the glomeruli and activate the classical pathway. Researchers have also identified additional mechanisms by which complement is activated in the kidney, including diseases in which the alternative and lectin pathways are activated. The kidney appears to be particularly susceptible to activation of the alternative pathway, and this pathway has been implicated as a primary driver of atypical hemolytic uremic syndrome, C3 glomerulopathy, anti-neutrophil cytoplasmic antibody-associated vasculitis, as well as some forms of immune-complex glomerulonephritis. In this paper we review the shared and distinct mechanisms by which complement is activated in these different diseases. We also review the opportunities for using therapeutic complement inhibitors to treat kidney diseases.